Acceptance of COVID-19 vaccine and associated factors among health care workers at public hospitals in Eastern Ethiopia using the health belief model - Getachew, Tamirat; Lami, Magarsa; Eyeberu, Addis; Balis, Bikila; Debella, Adera; Eshetu, Bajrond; Degefa, Meron; Mesfin, Sinetibeb; Negash, Abraham; Bekele, Habtamu; Turiye, Getahun; Tamiru, Dawit; et al. (Frontiers in Public Health, 2022)
Introduction: Acceptance of vaccination among Health Care Workers is mandatory to lessen and curve the spread of transmission of COVID-19. Even though the Health Belief Model is one of the most widely used models for understanding vaccination behavior against COVID-19 disease, COVID-19 vaccine acceptance among Health Care Workers in Ethiopia was not adequately explored by using the Health Belief Model domains. Purpose: This study aimed to assess COVID-19 vaccine acceptance and associated factors among Health care workers in eastern, Ethiopia. Methods: Institutional-based cross-sectional study design was used among 416 health care workers selected by a systematic random sampling method from June 1- 30/2021. The data were collected by face-to-face interviews using semi-structured questionnaires and analyzed using STATA version 14 statistical software. Multivariable binary logistic regression analysis with a 95% confidence interval was carried out to identify factors associated with willingness to COVID-19 vaccine acceptance and a statistical significance was declared at a P-value < 0.05. Results: The willingness of health care workers to accept the COVID-19 vaccine was 35.6% making a response rate of 99.7%. Age 30-39 (AOR= 4.16;95% CI: 2.51, 6.88), age ≥ 40 years (AOR= 3.29;95% CI: 1.47, 7.39), good attitude (AOR=1.97; 95% CI: 1.00, 3.55), perceived susceptibility (AOR=1.93; 95% CI: 1.12, 3.32), and perceived severity (AOR=1.78; 95% CI: 1.03, 3.10) were factors significantly associated with Health Care Workers acceptance of COVID-19 vaccine. Conclusion: The willingness to accept the COVID-19 vaccine was low. Factors significantly associated with the willingness to accept the COVID-19 vaccine were age, good attitude, perceived susceptibility, and perceived severity of the disease. The low willingness of Health Care Workers to accept the COVID-19 vaccine was alarming and it needs more emphasis from the government in collaboration with other stakeholders to provide reliable information to avert misconceptions and rumors about the vaccine to improve the vaccine status of Health Care Workers to protect the communities.